2020
DOI: 10.1111/jre.12782
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of periodontitis and edentulism to angiographically diagnosed coronary artery disease: A cross‐sectional study

Abstract: Objective: The objective of the study is to examine the connection between oral status and the extent of coronary artery disease (CAD), which is diagnosed by angiography. Background: Periodontitis and tooth loss have been linked to atherosclerosis and CAD in previous studies. However, no distinct connection was revealed due to the diversity of the results and the variety of diagnostic methods. To provide a more consistent data pool and stronger evidence, there is a need for studies with standard measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…In agreement, a recent report [55] has evidenced that CRP was strictly correlated with PT, even after adjusting for some potential confounders [55][56][57]. For these reasons, during SSc, PT can lead to a negative systemic inflammatory stimulus and a relative augmented risk of endothelial dysfunction and focal ischemic injuries that, associated with SSc, may determine, in the heart tissues, myocytes apoptosis and fibroblasts replacement, with a final, irreversible myocardial fibrosis [56].…”
Section: Discussionsupporting
confidence: 75%
“…In agreement, a recent report [55] has evidenced that CRP was strictly correlated with PT, even after adjusting for some potential confounders [55][56][57]. For these reasons, during SSc, PT can lead to a negative systemic inflammatory stimulus and a relative augmented risk of endothelial dysfunction and focal ischemic injuries that, associated with SSc, may determine, in the heart tissues, myocytes apoptosis and fibroblasts replacement, with a final, irreversible myocardial fibrosis [56].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies mainly focused on the association between periodontitis and only 1 of the systemic conditions, such as cardiovascular disease (Larvin et al 2021a), hypertension (Czesnikiewicz-Guzik et al 2019), diabetes (Winning et al 2017), and COVID-19 outcomes (Larvin et al 2020; Larvin, Wilmott, et al 2021). Some studies demonstrated that periodontitis is coprevalent with several systemic conditions, such as obesity, diabetes, and cardiovascular disease, but these were predefined at study inclusion (Kang et al 2019; Bilgin Çetin et al 2020; Takeda et al 2021). Through use of hypergraph analysis as a data-driven technique, our study has identified some common systemic multimorbidity clusters in people with periodontitis and the most influential single diseases to multimorbid presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data indicate the close relationship of GP with cardiovascular diseases including coronary artery disease (CAD) [2,12,14,16,17,18,19]. CAD is a disease that combines angina, myocardial infarction, cardiosclerosis etc., and occurs due to narrowing of the coronary vessel lumen, often with subsequent thrombosis, which leads to insufficient oxygen supply to the heart muscle [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that GP may contribute to dysfunction and damage of blood vessels, including coronary arteries [2]. From this perspective, GP can act as an independent risk factor for CAD, along with common factors such as hypertension, diabetes, dyslipidemia, obesity, smoking, and others [1,12,14,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation